The trend towards healthy behavior among students of science and technology of physical activities and sport at the University of M’sila - بطاط نورالدين (sports creativity, 2025)
The study aimed to reveal the attitude towards healthy behavior among students of physical activity and sports sciences and technologies at the University of M'sila. It included a sample of 212 students out of a total of 2124 students who were chosen in a stratified proportional random manner, i.e., at a rate of 10 percent.